TOPENG SEBAGAI INSPIRASI DALAM KARYA SENI GRAFIS DENGAN TEKNIK RELIEF PRINT - M. HADI PUTRA, Dr. Budiwirman, M.Pd. Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2017)
Mask has its own charm, has a variety of unique types and shapes, each mask also has a variety of characteristics that reflect the nature of humans. The purpose of lifting about masks is through artwork, artists can convey messages and goals to be conveyed, because artwork is the language of an artist. Likewise with the author, through the final task entitled, "Topeng As Inspiration In Graphic Art Work With Relief Print Techniques" has the following objectives: Visualize the mask in various forms and different motions into the work of graphic art with relief print techniques. From the various search results, the authors create works with the title: searching, camouflage, selfish vs. true self, change, many roles, opposite, balloon, released, united, and opened.Keywords: Mask, Graphic Art, Print Relief.